In-session-reflective-functioning in anorexia nervosa: an analysis of psychotherapeutic sessions of the ANTOP Study - Zeeck, Almut; Taubner, Svenja; Gablonski, Thorsten C.; Lau, Inga; Zipfel, Stephan; Herzog, Wolfgang; Wild, Beate; Friederich, Hans-Christoph; Resmark, Gaby; Giel, Katrin; Teufel, Martin; Burgmer, Markus; et al. (Frontiers in psychiatry, 2022)
ObjectivePrevious research suggests that patients with anorexia nervosa (AN) show an impaired capacity to mentalize (reflective functioning, RF). RF is discussed as a possible predictor of outcome in psychotherapeutic processes. The study aimed to explore RF in sessions of patients with AN and its association with outcome and type of treatment.MethodsA post-hoc data analysis of selected cases from a randomized trial on outpatient psychotherapy for AN was conducted. Transcripts from 84 sessions of 28 patients (early phase, middle phase, and end of treatment) were assessed using the In-Session-Reflective-Functioning-Scale [14 cognitive-behavior therapy, enhanced (CBT-E); 14 focal psychodynamic therapy (FPT); 16 with good, 12 with poor outcome after 1 year]. Relations between the level of RF, type of treatment, and outcome were investigated using mixed linear models. Additionally, associations with depressive symptoms, weight gain, and therapeutic alliance were explored.ResultsMean in-session RF was low. It was higher in FPT when compared to CBT-E treatments. The findings point to an association between RF increase and a positive outcome. An increase in BMI in the first half of treatment was associated with higher subsequent in-session RF. There was no association between RF and depressive symptoms or the therapeutic alliance.DiscussionPatients with AN show a low capacity to mentalize in sessions, which seems to be at least partly dependent on the degree of starvation. The results suggest a possible relationship between an increase in in-session RF and outcome, which has to be replicated by further studies.